UPAYA MENINGKATKAN HASIL BELAJAR DRIBBLE BOLA BASKET MELALUI PENGGUNAAN MEDIA AUDIOVISUAL - Frilyandi Kurniawan; Budi Budi; Elang Fauzan (STKIP Muhammadiyah Kuningan, 2020)
This research has a goal in developing children's learning through audiovisual media. This research method is a Classroom Action Research. The population in this study were class VIII students of SMP Negeri 7 Kuningan, semester II of the 2019/2020 school year. Determination of the sample using purposive sampling technique with 32 people to be the research subjects. Data collection techniques by doing (observation) and documentation. The results of the analysis of the output table